Evaluating feeding strategies for microbial oil production from glycerol by Rhodotorula glutinis. Issue 3 (7th September 2016) - Karamerou, Eleni E.; Theodoropoulos, Constantinos; Webb, Colin
Abstract : Oil production, from biodiesel by‐product glycerol, through microbial fermentation provides a promising option as part of an integrated biorefinery process. However, bioprocessing improvements are required to make the process more efficient. In the present work, different glycerol feeding strategies were evaluated under fed‐batch cultivation of the oleaginous yeast Rhodotorula glutinis . Results showed that the concept of targeting first a cell proliferation stage and then a lipid accumulation stage had beneficial effects on both biomass and oil yields. Continual feeding and pulsed feedings, delivering the same total amount of nutrients, resulted in similar values of cellular biomass (∼25 g/L) and oil content (∼40%). In contrast, continual supply of nutrients at higher rates ( >0.8 g/L/h) led to an increase in both cell densities (30 g/L) and oil content (53%), attaining a high oil yield of 16.28 g/L. This suggests that a continual cultivation with two different rates for each stage constitutes an efficient approach to enhance microbial oil production.